Roads Old and New: Educational Strategies in University Choice by Russian Students - I. A. Skalaban; L. A. Osmuk; O. V. Kolesova; G. M. Cherepanov (Высшее образование в России)
This paper aims to explore the capabilities of new approaches to the study of educational demands on modern higher education market by describing existing educational strategies of applicants and students. The experience of university choice research in domestic and international practice consists of sufficiently popular description of educational demands, choice motivation and analysis of the choice-making process of university and specialty choice based on available information. The analysis of choice presented in the article is compounded by the description of the main educational strategies being formed on modern educational market, with an emphasis on their behavioral nature. Two following strategies are singled out: “status strategy”, where education acts primarily as an element of status and group identification; and “practical strategy” where education is viewed as an investment of time and resources into increasing one’s chances at the job market. Data gathered from the study of students of five universities of Tomsk and Novosibirsk aligns with these strategies, and this justifies the existence of an increasing divide in social-economic demography of higher education. Such tendency is capable of seriously affecting organizational strategies of universities and influence the very nature of higher education as a social institution by forcing universities and the system in general to take the given strategies into account.